THE INFLUENCE OF BODY POSITION ON THE SPEED OF A SIDE KICK IN KICKBOXING - Saulite, Sergejs; Popova, Anna; Pimenovs, Einars; Ciematnieks, Ugis; Bujak, Zbigniew; Gierczuk, Dariusz (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
Kickboxing is a combat sport where two types of fights occur: light-contact and full-contact. There is no limitation on the strength of kicks and punches in the latter type. In martial arts, athletes try to hit an opponent with as much speed and power as. The position of the upper body is indicated as the most important factor directly influencing the performance of the kicks. The aim of the research: to determine the effect of a change in the position of the upper body of a 14-16-year-old kickboxer on the time of execution of the side kick with the foot placed in front and the ground reaction force in the place, moving forward and in the counterattack, determining the time of the side kick and the ground reaction force of the take-off foot in three different upper body positions to give the execution time of each type of side kick and the ground reaction force of the take-off foot. The fastest side kick with the forward foot in place and moving forward will be in the upper body position 45° to the vertical axis, but performing side kick with the forward foot in counterattack and side kick moving forward from the position of the upper body 90˚ against the vertical axis was partially proved.